2008
DOI: 10.1152/ajpregu.00387.2007
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium glutamate-induced arcuate nucleus damage affects both natural torpor and 2DG-induced torpor-like hypothermia in Siberian hamsters

Abstract: Pelz KM, Routman D, Driscoll JR, Kriegsfeld LJ, Dark J. Monosodium glutamate-induced arcuate nucleus damage affects both natural torpor and 2DG-induced torpor-like hypothermia in Siberian hamsters. Am J Physiol Regul Integr Comp Physiol 294: R255-R265, 2008. First published March 1, 2007 doi:10.1152/ajpregu.00387.2007.-Siberian hamsters (Phodopus sungorus) have the ability to express daily torpor and decrease their body temperature to ϳ15°C, providing a significant savings in energy expenditure. Daily torpor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Increased peripheral glucose metabolism from VMH stimulation does not entail increased glucose transporters, in contrast to insulin-induced glucose uptake [38]. Associated with increased glucose metabolism, VMH stimulation also increases BAT temperature [39], likely reflecting hypothalamic mediation of hypothermia induced by 2DG [40]. Infusion of leptin specifically into the VMH also induces peripheral glucose metabolism [41] through enhancement of sympathetic nervous activity [42].…”
Section: Neurons Sensitive To Glucose Regulate Peripheral Glucose Andmentioning
confidence: 99%
“…Increased peripheral glucose metabolism from VMH stimulation does not entail increased glucose transporters, in contrast to insulin-induced glucose uptake [38]. Associated with increased glucose metabolism, VMH stimulation also increases BAT temperature [39], likely reflecting hypothalamic mediation of hypothermia induced by 2DG [40]. Infusion of leptin specifically into the VMH also induces peripheral glucose metabolism [41] through enhancement of sympathetic nervous activity [42].…”
Section: Neurons Sensitive To Glucose Regulate Peripheral Glucose Andmentioning
confidence: 99%
“…In photoperiodic hibernators (hamsters), there is evidence that the ARC is involved in mediating torpor, and that changes in nutrients within the ARC may be involved in the response (Pelz et al 2008). Using monosodium glutamate (MSG) to induce ARC neuronal damage, Pelz et al (2008) showed that MSG-treated animals did not enter torpor as frequently as controls under a short photoperiod.…”
Section: Behavioral Observations Of Food Intakementioning
confidence: 99%
“…Using monosodium glutamate (MSG) to induce ARC neuronal damage, Pelz et al (2008) showed that MSG-treated animals did not enter torpor as frequently as controls under a short photoperiod. Furthermore, food restriction-induced torpor was also reduced in MSG-treated animals.…”
Section: Behavioral Observations Of Food Intakementioning
confidence: 99%
“…26 Ablation of the arcuate nucleus abolishes torpor in Siberian hamsters and fasting-induced torpor in mice. 27 Ghrelin, a gut appetite hormone and neuropeptide activates NPY neurons in the arcuate nucleus and deepens torpor in mice. 28 These studies support the hypothesis that NPY Y1 receptor sites activated by NPY within the arcuate nucleus induce a torpor-like state through modulation of thermoregulation.…”
Section: Putative Endogenous Mediators Of Torpormentioning
confidence: 99%
“…28 These studies support the hypothesis that NPY Y1 receptor sites activated by NPY within the arcuate nucleus induce a torpor-like state through modulation of thermoregulation. 26, 27, 29 The efficacious orexigenic effect of NPY, however, is difficult to reconcile within the context of hibernation because onset of hibernation is preceded by a hypophagic period. 30 Indeed, TRH is the only member of the group of neuropeptides, well-known to regulate food intake that is upregulated in the hypothalamus during pre-hibernation satiety 30 .…”
Section: Putative Endogenous Mediators Of Torpormentioning
confidence: 99%